The Role Of Omega 3 Supplementation In Repeated Transient Ischemic Attack : A Case Report - Pretty Grace Zalukhu; Corry Ida Hinaya Zalukhu (International Medical Journal Corp. Ltd, 2024)
Introduction: According to a 2021 worldwide analysis, 1 in 4 adults will suffer a stroke in their lifetime. Risk factors include hypertension, diabetes mellitus, dyslipidemia, and atrial fibrillation. Lifestyle is a critical factor in stroke prevention. More importantly, dietary habits were shown to be the most relevant. To reduce the risk of ischemic stroke, nutritional approaches have historically focused on high-fiber diets with low in sodium, saturated fat, and cholesterol. It is well known that n-3 PUFAs reduce the risk of cardiovascular diseases. Case Report: A 65-years old woman present with headache and myalgia. She was grade I obese with a body weight of 69 kg. The patient has history of transient ischemic attack (TIA) twice within a year. There is a history of type 1 diabetes mellitus thus taking insulin for a year and hypertension for 2 years. On examination, the blood pressure was 170/90 mmHg. Both of her foot were swollen. Laboratory test results were normal. History of medication includes Amlodipine, Candesartan, Furosemide, dan Glargine. Omega 3 supplementation was planned to reduce inflammation and risk of future episodes of stroke. Conclusion: Omega-3 PUFA have various pharmacological activities, such as anti-inflammatory, anti-thrombosis, anti-atherosclerosis, reduce blood lipid levels and significantly improve endothelial dysfunction. Omega-3 is also beneficial in obesity and diabetics, which are risk factors of stroke or TIA.